Contribution of early Alzheimer's disease‐related pathophysiology to the development of acquired epilepsy. (19th June 2018) - Gschwind, Tilo; Lafourcade, Carlos; Gfeller, Tim; Zaichuk, Mariana; Rambousek, Lukas; Knuesel, Irene; Fritschy, Jean‐Marc
Abstract: Aberrant epileptic activity is detectable at early disease stages in Alzheimer's disease (AD) patients and in AD mouse models. Here, we investigated in young ArcticAβ mice whether AD‐like pathology renders neuronal networks more susceptible to the development of acquired epilepsy induced by unilateral intrahippocampal injection of kainic acid (IHK). In this temporal lobe epilepsy model, IHK induces a status epilepticus followed after two weeks by spontaneous recurrent seizures (SRS). ArcticAβ mice exhibited more severe status epilepticus and early onset of SRS. This hyperexcitable phenotype was characterized in CA1 neurons by decreased synaptic strength, increased kainic acid‐induced LTP and reduced frequency of spontaneous inhibitory currents. However, no difference in neurodegeneration, neuroinflammation, axonal reorganization or adult neurogenesis was observed in ArcticAβ mice compared to wild‐type littermates following IHK‐induced epileptogenesis. Neuropeptide Y (NPY) expression was reduced at baseline and its IHK‐induced elevation in mossy fibres and granule cells was attenuated. However, although this alteration might underlie premature seizure onset, neutralization of soluble Aβ species by intracerebroventricular Aβ‐specific antibody application mitigated the hyperexcitable phenotype of ArcticAβ mice and prevented early SRS onset. Therefore, the development of seizures at early stages of AD is mediated primarily by Aβ species causing widespread changes in synaptic function. Abstract : Arctic Aβ mice, a model of familial Alzheimer's disease are more susceptible to epileptogenic stimuli. Neutralization of soluble Aβ species normalizes their phenotype, suggesting that Aβ interferes with GABAergic transmission.